2013
DOI: 10.1248/bpb.b12-00654
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antiarrhythmic Effect of Methyl 3,4,5-Trimethoxycinnamate, a Bioactive Substance from Roots of <i>Polygalae Radix</i>: Suppression of Triggered Activities in Rabbit Myocytes

Abstract: 3,4,5-Trimethoxycinnamic acid (TMCA), methyl 3,4,5-trimethoxycinnamate (M-TMCA) and p-methoxycinnamic acid (PMCA) have been identified as the major bioactive components in the serum collected from rats treated with oral administration of Polygalae Radix ("YuanZhi," the roots of Polygala tenuifolia Willd.), a traditional Chinese medicine used to relieve insomnia, anxiety and heart palpitation. The present study was designed to investigate its direct electrophysiological effects on isolated ventricular myocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Inflammation and oxidative stress are closely related to arrhythmia [46][47][48]. Moreover, Radix Polygalae plays an antiarrhythmic role by inhibiting the triggered activities in cardiomyocytes [45]. All of these findings suggest the antiarrhythmic mechanisms of DFD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Inflammation and oxidative stress are closely related to arrhythmia [46][47][48]. Moreover, Radix Polygalae plays an antiarrhythmic role by inhibiting the triggered activities in cardiomyocytes [45]. All of these findings suggest the antiarrhythmic mechanisms of DFD.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, with the development of mass spectrometry, multiple constituents of the components of DFD have been analyzed and characterized in recent years [29][30][31][32][33][34]. Modern pharmacological studies have shown that the components of DFD have anti-inflammatory [35][36][37][38][39], antioxidative stress [40][41][42], and myocardial protection [42][43][44][45] effects. Inflammation and oxidative stress are closely related to arrhythmia [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Through screening of our library of natural product extracts from Chinese medicinal herbs, it was demonstrated that both Radix Polygalae and its single component, onjisaponin B, are able to induce autophagy with potential therapeutic application in modulating neurodegeneration. With a long history of use in traditional Chinese medicine to relieve insomnia, anxiety and heart palpitation [33], Radix Polygalae and its active components were proved to be capable of improving learning and memory of aged mice [34,35], attenuating hepatic ischemia-reperfusion induced cognitive dysfunction [36], inhibiting toxin-induced neuronal death in the Parkinson’s disease models [37], as well as having cerebral protective and cognition-improving effects [38]. Therefore, the study of the neuro-protective mechanisms and therapeutic applications of Radix Polygalae and its active components would be important for novel drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Zhao et al [29] presented that one of the major metabolite of P. tenuifolia in rat, 3,4,5-trimethoxycinnamate (N6), at the dosage of 15e30 mM markedly shortened APD50 (action potential duration at 50% repolarization) and APD90 (action potential duration at 90% repolarization) in cardiomyocytes in a concentrationdependent and a reversible manner ( Fig. 4).…”
Section: Biological Activities Of Natural Tmca Ester and Amide Derivamentioning
confidence: 99%